2013
DOI: 10.2147/ndt.s43461
|View full text |Cite
|
Sign up to set email alerts
|

Elevated factor VIII level and stroke in patients without traditional risk factors associated with cardiovascular diseases

Abstract: IntroductionHemostasis is affected by interactions between physiological processes, including those connected with the coagulation system, whose essence is converting fibrinogen into fibrin. The role of factor VIII (FVIII) consists in activating factor X, which directly participates in the generation of thrombin, which is able to produce stable fibrin, which in turn forms blood clots. There are divergent opinions regarding the significance of high levels of FVIII in stroke pathogenesis.AimThe aim of our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…11 Another study found that in patients who had suffered a stroke, those with elevated factor VIII levels were more likely to show evidence of a carotid or cerebral thrombus and presented with more disability when compared with those patients with normal levels of factor VIII. 12 Our case is unique among those in the literature, as the patient was significantly older than what has been documented thus far. We postulate that changes in the coagulation cascade after surgery precipitated these events.…”
Section: Discussionmentioning
confidence: 67%
“…11 Another study found that in patients who had suffered a stroke, those with elevated factor VIII levels were more likely to show evidence of a carotid or cerebral thrombus and presented with more disability when compared with those patients with normal levels of factor VIII. 12 Our case is unique among those in the literature, as the patient was significantly older than what has been documented thus far. We postulate that changes in the coagulation cascade after surgery precipitated these events.…”
Section: Discussionmentioning
confidence: 67%
“…Kamphuisen stated that only 4% of factor VIII activity >123% may cause the incidence of arterial thrombosis. 13 High factor-VIII activity is the risk factor of thrombosis, with a greater impact on venous thrombosis than arterial thrombosis. 15 In this study, factor VIII activity between O and non-O blood types was not significantly different.…”
Section: Results and Disccusionmentioning
confidence: 99%
“…5 The mechanism of genetic and environmental factors, that leads to a high factor VIII activity, as the cause of thrombosis, is not yet fully known. [13][14][15]…”
Section: Results and Disccusionmentioning
confidence: 99%
See 2 more Smart Citations